Examining Brand Experience, Brand Trust, and Customer Satisfaction as Predictors of Loyalty in Halal Skincare Products - Nandita, Wanda Vidya; Setyawan, Anton Agus (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of brand experience, brand trust, and customer satisfaction on brand loyalty in halal skincare products. Additionally, this research explores the mediating role of customer satisfaction in the relationship between brand experience and brand loyalty. This study employs a quantitative approach, collecting data through an online questionnaire distributed to consumers of the halal skincare brand Somethinc. The data collected was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results indicate that brand experience, brand trust, and customer satisfaction have a positive and significant influence on brand loyalty. Furthermore, customer satisfaction significantly mediates the relationship between brand experience and brand loyalty. This study has several limitations, including its focus on a single halal skincare brand, Somethinc, making it difficult to generalize the findings to other brands. Additionally, the cross-sectional approach used does not allow for observing long-term changes in brand loyalty. This research contributes to both academics and marketing practitioners by providing insights into the factors influencing brand loyalty in halal skincare products. The findings can be used by companies to enhance their marketing strategies by strengthening brand experience, building customer trust, and improving satisfaction to maintain customer loyalty.